(untitled) (Eurasian Journal of Philology Science and Education, 2025)
Research related to the theoretical and practical foundations of linguistic examination of verbal extremism is in demand when preventing negative political situations in various countries and addressing issues of state security. Therefore, the study of extremist conflict-prone publications as a linguistic product that is distributed among the population through the media is relevant not only for the development of such fields of science as jurisprudence, linguoexpertology, but at the same time it is also relevant at the level of state security. In this regard, the article examines issues of court cases that are within the professional competence of an expert linguist, based on the general concept of extremism and signs of verbal extremism as a linguistic product, on controversial materials of verbal extremism. The meaning of the term verbal extremism, located at the intersection of the spheres of language and law, is analyzed on the basis of the relevant articles of the Law of the Republic of Kazakhstan “On Combating Extremism” and the Criminal Code. The differences between the concepts of critical statements or conflict-generating publications and verbal extremism associated with political organizations, ideological and religious associations or religious beliefs, national or religious traditions are systematized. Also, the results of the study related to the mutual differentiation of the concepts of verbal extremism and hate speech have a positive impact on the objective decision of the linguistic examination of controversial material on verbal extremism in a court case. Keywords: verbal extremism, hate speech, linguistic expertise, call for aggressive actions, justification of aggressive actions, illocutionary act.